Crystal structure of single phase and low sintering temperature of α-cordierite synthesized from talc and kaolin - Banjuraizah, Johar; Hasmaliza, Mohamad; Zainal Arifin, Ahmad (Elsevier B.V., 2009)
Link to publisher's homepage at www.elsevier.com